2013
DOI: 10.1038/leu.2013.172
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide studies in multiple myeloma identify XPO1/CRM1 as a critical target validated using the selective nuclear export inhibitor KPT-276

Abstract: RNA interference screening identified XPO1 (exportin 1) among the 55 most vulnerable targets in multiple myeloma (MM). XPO1 encodes CRM1, a nuclear export protein. XPO1 expression increases with MM disease progression. Patients with MM have a higher expression of XPO1 compared with normal plasma cells (P<0.04) and to patients with monoclonal gammopathy of undetermined significance/smoldering MM (P< 0.0001). The highest XPO1 level was found in human MM cell lines (HMCLs). A selective inhibitor of nuclear export… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
143
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 30 publications
(55 reference statements)
3
143
0
Order By: Relevance
“…Small molecule, selective inhibitors of nuclear export (SINE) force nuclear retention of deregulated targets by preventing XPO1/ cargo interaction, thereby reestablishing normal tumor suppressive functions and rendering cancer cells responsive to other chemotherapeutics. We and others have demonstrated the cytotoxic effects of SINE in multiple myeloma (4)(5)(6)(7). Currently, multiple phase I/II clinical trials are enrolling to test the efficacy of the orally available SINE, selinexor, in patients with advanced stage pancreatic, prostate, salivary gland, and rectal cancers, glioblastoma, melanoma, non-Hodgkin's lymphoma, acute myeloid leukemia, and relapsed/refractory multiple myeloma (R/R multiple myeloma).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Small molecule, selective inhibitors of nuclear export (SINE) force nuclear retention of deregulated targets by preventing XPO1/ cargo interaction, thereby reestablishing normal tumor suppressive functions and rendering cancer cells responsive to other chemotherapeutics. We and others have demonstrated the cytotoxic effects of SINE in multiple myeloma (4)(5)(6)(7). Currently, multiple phase I/II clinical trials are enrolling to test the efficacy of the orally available SINE, selinexor, in patients with advanced stage pancreatic, prostate, salivary gland, and rectal cancers, glioblastoma, melanoma, non-Hodgkin's lymphoma, acute myeloid leukemia, and relapsed/refractory multiple myeloma (R/R multiple myeloma).…”
Section: Introductionmentioning
confidence: 91%
“…One manner in which these proteins may be dysregulated is via mislocalization within the cell. Exportin 1 (XPO1; or chromosome maintenance region 1, CRM1) is the prominent nuclear export receptor that controls nucleo-cytoplasmic localization of many proteins (2) and is overexpressed in many cancer types both solid and hematologic in origin, including multiple myeloma as shown by us and others (4)(5)(6), promoting aberrant cytoplasmic accumulation of its cargo. Small molecule, selective inhibitors of nuclear export (SINE) force nuclear retention of deregulated targets by preventing XPO1/ cargo interaction, thereby reestablishing normal tumor suppressive functions and rendering cancer cells responsive to other chemotherapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…CRM1 is upregulated in several types of cancer, and its overexpression correlates with a poor prognosis (11,(13)(14)(15)(16)(17). Importantly, CRM1 inhibition by the potent small-molecule selective inhibitor of nuclear export (SINE), KPT-330, has been suggested as a promising therapeutic option for a number of cancer types (18)(19)(20)(21)(22)(23). In this study, we characterized the biologic significance of CRM1 in the context of EWS and determined the therapeutic merit of CRM1 inhibition for this malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of KPT-185 with bortezomib showed synergistic effect on growth arrest in MM cells. However, no synergy was observed with KPT-276 when combined with other chemotherapeutic agents such as bortezomib, dexamethasone and melphalan in a different studies [49] . Interesting, this study found that SINEs suppressed the expression of cell division cycle 25 homolog A, bromodomain-containing protein 4 (BRD4) and c-Myc [49] .…”
Section: Role Of Selective Inhibitors Of Nuclear Export (Xpo1 Inhibitmentioning
confidence: 88%
“…However, no synergy was observed with KPT-276 when combined with other chemotherapeutic agents such as bortezomib, dexamethasone and melphalan in a different studies [49] . Interesting, this study found that SINEs suppressed the expression of cell division cycle 25 homolog A, bromodomain-containing protein 4 (BRD4) and c-Myc [49] . Moreover, combined treatment with selinexor and carfilzomib caused significant apoptosis of myeloma cells and primary plasma cells derived from relapsing/refractory myeloma patients [50] .…”
Section: Role Of Selective Inhibitors Of Nuclear Export (Xpo1 Inhibitmentioning
confidence: 88%